A review of research on China's carbon emission peak and its forcing mechanism. Issue 1 (2nd January 2018) - Wang, Feng; Yang, Fang
ABSTRACT: In order to make further steps in dealing with climate change, China proposed to peak carbon dioxide emissions by about 2030 and to make best efforts for the peaking early. The carbon emission peak target (CEPT) must result in a forcing mechanism on China's economic transition. This paper, by following the logical order from "research on carbon emission history" to "carbon emission trend prediction, " from "research on paths of realizing peak" to "peak restraint research, " provides a general review of current status and development trend of researches on China's carbon emission and its peak value. Furthermore, this paper also reviews the basic theories and specific cases of the forcing mechanism. Based on the existing achievements and development trends in this field, the following research directions that can be further expanded are put forward. First, from the perspective of long-term strategy of sustainable development, we should analyze and construct the forcing mechanism of CEPT in a reverse thinking way. Second, economic transition paths under the forcing mechanism should be systematically studied. Third, by constructing a large-scale policy evaluation model, the emission reduction performance and economic impact of a series of policy measures adopted during the transition process should be quantitatively evaluated.